Legal Protection ofr Heir of Account Owners Unlawfully Blocked By The Banks - Wijaya Wijaya; Yurisa Martanti; Taqiyuddin Kadir (Journal of Innovative and Creativity, 2025)
The study purpose was to examine the legal protection for heirs of account owners whose bank accounts are unlawfully blocked by banks without a valid court decision or the consent of the heirs. This issue arises because such actions contradict the principle of prudence in banking operations and may cause losses to the heirs, thus raising questions regarding the authority of banks and the legal remedies available. The research aims to analyze: (1) the authority of banks to block the accounts of deceased customers against their heirs; and (2) the legal protection available to heirs when banks commit unlawful blocking of accounts. This research employed a normative juridical legal research method, relying on secondary data obtained from primary, secondary, and tertiary legal sources. The approaches used included the Legislation Approach, Case Approach, Analytical Approach, and Conceptual Approach. Data were collected through literature study, identifying and inventorying statutory regulations, legal doctrines, and relevant case studies. The legal analysis techniques applied consisted of Grammatical Interpretation, Systematic Interpretation, and legal construction methods. The findings demonstrate that banks have no authority to unilaterally block the accounts of deceased customers, as this contradicts Article 29 paragraph (3) of Law Number 10 of 1998 concerning Banking. The action is deemed unlawful since it disregards the principle of prudence and the obligation to protect customer rights. Heirs who suffer losses due to such acts are entitled to legal protection and may file a civil lawsuit under Article 1365 of the Indonesian Civil Code to demand recognition and restoration of their rights. The study concludes that unilateral blocking of deceased customers’ accounts by banks constitutes an unlawful act. Legal protection for heirs is available through civil remedies, ensuring the protection of property rights and upholding justice in banking practices.